(untitled) (The Pakistan Development Review, 2012)
Financial services sector has become a major driver of economic growth in the developing countries through innovation in response to the forces of globalisation and technology. Sound risk management practices by financial institution are critical to the stability of the institutions and to the sustainability of economic growth. Therefore, measurement of market risk is important to all market participants for devising risk management strategies. Value-at-Risk (VaR) is the most widely used measure of market risk, which is defined as the maximum possible loss to the value of financial assets with a given probability over a certain time horizon. However, the task of implementing the VaR approach still remains a challenge as the empirical return distributions are found to be fat tailed and skewed in contrast to the normal distribution as assumed in the theoretical models. An extensive literature in finance (e.g., Nassim Taleb’s The Black Swan) underscores the importance of rare events in asset pricing and portfolio choice. These rare events may materialise in the shape of a large positive or negative investment returns, a stock market crash, major defaults, or the collapse of risky asset prices.